Improving self-confidence in rhythmic movement through game-based learning with an inclusive anti-gender bias approach: classroom action research - muhammad adlian ashafiq; Perdinanto; Ahmad Syarif (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2026)
Abstract: Low self-confidence in rhythmic movement activities is a common challenge in Physical Education (PE), particularly among junior high school students who are influenced by gender stereotypes. This Classroom Action Research (CAR) aimed to describe and analyze the improvement of self-confidence among Grade VII students of SMPN 13 Banjarbaru in rhythmic movement activities through Game Based Learning (GBL) integrated with an inclusive anti-gender bias approach. The study followed the Kemmis and McTaggart spiral model across two cycles, each consisting of one learning session (3 x 40 minutes). Participants were 30 students (14 male, 16 female) in the 2025/2026 academic year. Data were collected using a self-confidence questionnaire (35 Likert-scale items, maximum score 175) and an observational rubric (scale 1–4) administered in parallel across three stages: Pre-Cycle, Cycle I, and Cycle II. The success indicator was set at 76% of students achieving the proficient category on both instruments. Results showed a significant improvement from Pre-Cycle to Cycle II. Questionnaire data indicated that 80% of students reached the high confidence category (mean score 140.47 or 80.27% of maximum), with a cumulative N-Gain of 0.365 (moderate category). Observational data recorded 80% of students achieving the proficient threshold (mean score 3.47 out of 4). The convergence of both instruments confirmed that the GBL-inclusive anti-gender bias approach effectively enhanced self-confidence in rhythmic movement activities. These findings offer a practical model for PE teachers to design gender-responsive and student-centered learning environments.